Pemaknaan Pesan Komunikasi Iklan Produk Perawatan Pria Terkait Stigma di Masyarakat - Hernanda, Jocelyn Amantha; Utami, Lusia Savitri Setyo (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
The development of increasingly creative advertisements makes companies make their advertisements with social messages in them to attract attention and also be easy for audiences to understand. Like what MS GLOW FOR MEN did, it hooked Marshell Widianto and Babe Cabita as the stars of its advertisement to carry out a campaign against the stigma of beauty standards in society. This study aims to find out and describe the meaning of beauty product advertising communication messages for men related to the stigma of beauty standards in society. To obtain this meaning, the researcher uses the theory of advertising communication messages, the stigma of public beauty standards, and the concept of audience meaning. This research uses a qualitative approach with a case study method. Researchers obtained the information needed through interviews and observations of four informants, documentation and literature studies. The results of the research that has been carried out by researchers is that there is a meaning in the communication message in the MS GLOW FOR MEN advertisement which invites the public to no longer be fixated on the existence of beauty standards in society. In terms of the four informants who agreed to the campaign carried out by the MS GLOW FOR MEN advertisement. At present, it is seen that the stigma of beauty standards in today's society has begun to be removed. Perkembangan iklan yang semakin kreatif membuat perusahaan memproduksi iklan dengan konten pesan sosial di dalamnya untuk menarik perhatian dan juga lebih mudah dipahami oleh khalayak. Seperti yang dilakukan MS GLOW FOR MEN, menggaet Marshell Widianto dan Babe Cabita sebagai bintang iklannya untuk melakukan kampanye melawan stigma standar kecantikan di masyarakat. Penelitian ini bertujuan untuk mengetahui dan mendeskripsikan makna pesan komunikasi iklan produk kecantikan bagi pria terkait stigma standar kecantikan di masyarakat. Untuk memperoleh makna tersebut, peneliti menggunakan konsep pesan komunikasi periklanan, stigma standar kecantikan masyarakat, dan konsep makna khalayak. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Peneliti memperoleh informasi yang dibutuhkan melalui wawancara dan observasi terhadap empat informan, pemeriksaan dokumen dan studi literatur. Hasil penelitian yang telah dilakukan peneliti adalah terdapat makna pesan komunikasi dalam iklan MS GLOW FOR MEN yang mengajak masyarakat untuk tidak lagi terpaku dengan adanya standar kecantikan yang ada di masyarakat. Dilihat dari empat informan yang menyetujui kampanye iklan MS GLOW FOR ME, terlihat stigma standar kecantikan di masyarakat mulai berubah.